2004
DOI: 10.1002/ejlt.200400953
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties of polyphenol‐containing extract from soybean fermented with Saccharomyces cerevisiae

Abstract: The antioxidant properties and total phenolic compounds of soybean extract fermented with Saccharomyces cerevisiae during 24 h were evaluated. Total polyphenolic compounds extracted in ethanol/water (1:1) solution were 789.54 mg/g dry extract, and flavonoids were 169.47 mg quercetin equivalents/g of dry extract. Reducing power (91.18%) and DPPH scavenging (79.30% at 4-times diluted) were excellent, and so high as BHA, 92.17% and 73.8% respectively, while superoxide anion scavenging showed poor inhibition (4876… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 23 publications
3
30
0
Order By: Relevance
“…Similar observations were reported in previous studies [16,20]. Thus, in the study carried out by Wang et al [21], various concentrations of ethanol ranging from 15% to 96% were investigated for the extraction of phenolic compounds such as rosmarinic and caffeic acids from some herbs and ethanol concentrations between 30% and 60% were found to give the highest extraction yields for both compounds.…”
Section: Polyphenol Contentsupporting
confidence: 84%
“…Similar observations were reported in previous studies [16,20]. Thus, in the study carried out by Wang et al [21], various concentrations of ethanol ranging from 15% to 96% were investigated for the extraction of phenolic compounds such as rosmarinic and caffeic acids from some herbs and ethanol concentrations between 30% and 60% were found to give the highest extraction yields for both compounds.…”
Section: Polyphenol Contentsupporting
confidence: 84%
“…In some cases the antioxidant effect could be significantly enhanced through fermentation using aspergilli (Esaki, Onozaki, Kawakishi, & Osawa, 1997;Lin, Wei, & Chou, 2006;Romero, Doval, Sturla, & Judis, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the antioxidant activity of soybeans considerably increases after fermentation (Romero, Doval, Sturla, & Judis, 2004;Wardhani, Vazquez, & Pandiella, 2009). Although the antioxidant activity of unfermented and fermented soybeans has been studied, information related to their application in different model foods remains limited.…”
Section: Introductionmentioning
confidence: 99%